2009
DOI: 10.2746/042516408x343019
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of radiography and ultrasonography to detect osteochondrosis lesions in the tarsocrural joint: A prospective study

Abstract: Radiographic examination should include a dorso30 degrees view for detection of lesions on the medial malleolus and ultrasonography should be considered to diagnose osteochondrosis in the tarsocrural joints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 13 publications
0
24
0
2
Order By: Relevance
“…The use of multiple radiographic projections to identify lesions in different locations of the same joint has been previously recommended in the tarsus of the horse. 8 Other authors suggested the LM view of the stifle is the best for detecting osteochondrosis lesions of the medial trochlear ridge and the Ca60 • L-CrMO view is the best for detecting lateral trochlear ridge lesions. 5 The oblique projection reduces superimposition of the trochlear ridges, 1, 5 and consequently improves visualization of the subchondral bone contour and opacity of the lateral trochlear ridge.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The use of multiple radiographic projections to identify lesions in different locations of the same joint has been previously recommended in the tarsus of the horse. 8 Other authors suggested the LM view of the stifle is the best for detecting osteochondrosis lesions of the medial trochlear ridge and the Ca60 • L-CrMO view is the best for detecting lateral trochlear ridge lesions. 5 The oblique projection reduces superimposition of the trochlear ridges, 1, 5 and consequently improves visualization of the subchondral bone contour and opacity of the lateral trochlear ridge.…”
Section: Discussionmentioning
confidence: 98%
“…Fifty false-positive joints also were identified in a previous study that compared ultrasonography and radiography for detection of articular lesions of several joints. 7 As previously reported, [7][8][9] arthroscopy was used as the reference standard to determine the presence of the lesions and to evaluate their severity. Arthroscopy allows evaluation of surfaces of the synovial membrane, articular cartilage, and intra-articular ligaments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, radiography may be less sensitive than ultrasonography for detecting some OC lesions in the tarsocrural joint (Relave and others 2009) and radiography was considered inaccurate in diagnosing lesions of the lateral trochlear ridge of the talus treated arthroscopically (McIlwraith 1993). It appears that no survey of the incidence of tarsocrural effusion has been published, although it is reportedly common in Draft horses (Goble 1993).…”
mentioning
confidence: 99%
“…Defeitos do osso subcondral devem ser examinados cuidadosamente em potros, especialmente em áreas onde a ossificação endocondral ocorre tardiamente (RICHARDSON, 2002). Se uma lesão é identificada, a articulação contralateral deve ser examinada radiograficamente, devido ao envolvimento bilateral, ou até os quatro membros em se tratando de articulação metacarpo/ metatarsofalangeana (COLÓN et al, 2000 O exame ultrassonográfico apresenta maior sensibilidade para detecção de lesões não mineralizadas, porém possui algumas limitações, como permitir apenas uma avaliação superficial da articulação e depender da eficiência do operador (RELAVE et al, 2009). …”
Section: Diagnóstico Na Ocdunclassified